An Eleven Months Old Infant with Very Early Onset Inflammatory Bowel Diseases (IBD): A Rare Case Report (Bangladesh Medical Journal, 2022)
Inflammatory bowel disease (IBD) in pediatric cases has been seen rapidly increasing in number over the last decade. Now a days four types of pediatric IBD has been identified: less than ten years of age - early onset IBD, less than six years of age - very early onset IBD, less than two years of age- infantile IBD and less than twenty eight days of age - neonatal onset IBD. Young children presented with more aggressive clinical features and severity is more than the older children and adults. Early onset disease presenting in children may have a monogenic basis. Infantile IBD or neonatal IBD having the high rates to affect the first-degree relatives and there is very high chance to develop resistance against immunosuppressive treatment. Very early onset IBD (VEO-IBD) most commonly presenting per rectal bleeding with or without mucous stools, isolated colonic disease, perianal involvement, skin lesions, whereas early onset IBD (EO-IBD) commonly presented with abdominal pain and weight loss. A thorough history, physical examination, biochemical markers, endoscopic evaluation with macroscop and microscopic findings are the only way to reach the diagnosis. The treatment of VEO-IBD is the same as that given to the adolescents and adults with IBD (eg, anti-inflammatory agents, immunomodulators, biologics, antibiotics, and surgical approaches). Here, we report a rare case of very early onset IBD of a 11 months old male infant, who presented with the complaints of blood and mucus mixed loose watery stool for 10 days, having similar episodes for last five months. He was mildly pale, and had thrombocytosis with raised C reactive protein (CRP), features of colitis in stool routine microscopic test. The diagnosis was confirmed by colonoscopy and histopathology study, which showed features of Crohn’s colitis. He was treated by anti-inflammatory drugs (steroid and mesalazine) with a significant improvement in a short time.Bangladesh Med J. 2021 May; 50(2) : 45-49